Metagenomic sequencing reveals the taxonomic and functional characteristics of rumen microorganisms in Dongliu buffalo - Wenwen Lu; Jinling Hua; Min Zhang; Longfei Yan; Huwei Zhao; Xiaokang Lv (Scientific Reports)
Abstract In this study, the composition of the rumen microbiota and its functional characteristics were investigated using a metagenomic approach in Dongliu buffalo. This study compared the rumen microbial communities of six female and four male Dongliu buffaloes of similar age, weight and lifestyle. Taxonomic analysis identified 964 genera across 52 phyla, dominated by Bacteroidota (47.54%) and Bacillota (28.20%). While alpha and beta diversity showed no sex differences (PERMANOVA P = 0.82), males exhibited higher Fibrobacter at the genus level (P = 0.02). Functional profiling revealed 429 KEGG pathways, with carbohydrate metabolism (11.17%) and amino acid metabolism (9.74%) as dominant processes. Males showed enrichment in cellulose-degrading enzymes (EC2.4.1.20, EC1.2.1.90, EC2.7.1.58) and CAZymes (GH94, GT35), while females had higher Bacteroides abundance (P = 0.01) and CAZymes like CBM47. Core cellulolytic genera (Prevotella, Ruminococcus) demonstrated male-biased GH/CBM activity, linked to enhanced fiber degradation. COG annotation highlighted carbohydrate metabolism as central, with sex-specific functional partitioning in replication (female-enriched) and secondary metabolism (male-enriched). Network analysis revealed Prevotella’s dominance in CAZymeme contributions and functional specialization in lignocellulose degradation pathways, suggesting sex-driven microbial adaptation to dietary fiber utilization.